ApoA-I Mimetic Peptide Reduces Vascular and White Matter Damage After Stroke in Type-2 Diabetic Mice - Wang, Xiaohui; Li, Rongwen; Zacharek, Alex; Landschoot-Ward, Julie; Chopp, Michael; Chen, Jieli; Cui, Xu (Frontiers in Neuroscience, 2019)
Diabetes leads to an elevated risk of stroke and worse functional outcome compared to the general population. We investigate whether L-4F, an economical ApoA-I mimetic peptide, reduces neurovascular and white-matter damage in db/db type-2 diabetic (T2DM) stroke mice. L-4F (16mg/kg, subcutaneously administered initially 2h after stroke and subsequently daily for 4 days) reduced hemorrhagic transformation, decreased infarct-volume and mortality, and treated mice exhibited increased cerebral arteriole diameter and smooth muscle cell number, decreased blood-brain barrier leakage and white-matter damage in the ischemic brain as well as improved neurological functional outcome after stroke compared with vehicle-control T2DM mice (p<0.05, n=11/group). Moreover, administration of L-4F mitigated macrophage infiltration, and reduced the level of proinflammatory mediators tumor necrosis factor alpha (TNFα), high-mobility group box-1 (HMGB-1)/ advanced glycation end-product receptor (RAGE) and plasminogen activator inhibitor-1 (PAI-1) in the ischemic brain in T2DM mice (p<0.05, n=6/group). In vitro, L-4F treatment did not increase capillary-like tube formation in mouse-brain endothelial cells, but increased primary artery explant cell migration derived from C57BL/6-aorta 1 day after middle cerebral artery occlusion (MCAo), and enhanced neurite-outgrowth after 2h of oxygen-glucose deprivation and axonal-outgrowth in primary cortical neurons derived from the C57BL/6-embryos subjected to high-glucose condition. This study suggests that early treatment with L-4F provides a potential strategy to reduce neuroinflammation and vascular and white-matter damage in the T2DM stroke population.